Analysis of spatial planning solutions for civil protection structures according to regulatory requirements - Filonenko , Olena; Yurchenko, Ihor; Lvovska Тetiana; Mahas, Nataliia (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article presents an analysis of the normative-legal documentation regulating the construction and reconstruction of civil protection shelters in countries such as Israel and Ukraine. A comparative analysis method was employed to identify the differences in shelter requirements between the two countries. Specific technical requirements that significantly impact the design and construction process were highlighted. The study compared the approach to determining the required area of shelters in both countries for various facilities. An overview and description of the requirements for ventilation systems, water supply, drainage, and electrical connections were provided. Additionally, the general approach to selecting finishing materials and types of coverings for internal and external structural elements was described. Significant discrepancies in the requirements and approaches to the construction or reconstruction of shelters in these countries were identified. The findings can be used to enhance the efficiency of shelter design and construction in Ukraine, which is particularly relevant in the current context of increased risks to the civilian population.